Exosomes from Suxiao Jiuxin pill-treated cardiac mesenchymal stem cells decrease H3K27 demethylase UTX expression in mouse cardiomyocytes in vitro - RUAN Xiao-fen; LI Yong-jun; JU Cheng-wei; SHEN Yan; LEI Wei; CHEN Can; LI Yang; YU Hong; LIU Yu-tao; KIM Ilman; WANG Xiao-long; WEINTRAUB Neal L; et al. (Acta Pharmacologica Sinica, 2018)
Abstract Suxiao Jiuxin pill (SJP) is a traditional Chinese medicine for the treatment of acute coronary syndrome in China, which contains two principal components, tetramethylpyrazine (TMP) and borneol (BOR). Thus far, however, the molecular mechanisms underlying the beneficial effects of SJP on the cardiac microenvironment are unknown. Cardiac mesenchymal stem cells (C-MSCs) communicate with cardiomyocytes (CMs) through the release of microvesicles (exosomes) to restore cardiac homeostasis and elicit repair, in part through epigenetic regulatory mechanisms. In this study, we examined whether SJP treatment altered C-MSC-derived exosomes (SJPExos) to cause epigenetic chromatic remodeling in recipient CMs. C-MSC isolated from mouse hearts were pretreated with SJP (SJPExos), TMP (TMP-Exos) or BOR (BOR-Exos). Then, HL-1 cells, a mouse cardiomyocyte line, were treated with exosomes from control C-MSCs (Ctrl-Exos), SJP-Exos, TMP-Exos or BOR-Exos. Treatment with SJP-Exos significantly increased the protein levels of histone 3 lysine 27 trimethylation (H3K27me3), a key epigenetic chromatin marker for cardiac transcriptional suppression, in the HL-1 cells. To further explore the mechanisms of SJP-Exo-mediated H3K27me3 upregulation, we assessed the mRNA expression levels of key histone methylases (EZH1, EZH2 and EED) and demethylases (JMJD3 and UTX) in the exosome-treated HL-1 cells. Treatment with SJP-Exo selectively suppressed UTX expression in the recipient HL-1 cells. Furthermore, PCNA, an endogenous marker of cell replication, was significantly higher in SJP-Exo-treated HL-1 cells than in Ctrl-Exo-treated HL-1 cells. These results show that SJP-Exos increase cardiomyocyte proliferation and demonstrate that SJP can modulate C-MSC-derived exosomes to cause epigenetic chromatin remodeling in recipient cardiomyocytes; consequently, SJP-Exos might be used to promote cardiomyocyte proliferation.